2013
DOI: 10.1007/s00442-013-2737-1
|View full text |Cite
|
Sign up to set email alerts
|

Insect density–plant density relationships: a modified view of insect responses to resource concentrations

Abstract: Habitat area is an important predictor of spatial variation in animal densities. However, the area often correlates with the quantity of resources within habitats, complicating our understanding of the factors shaping animal distributions. We addressed this problem by investigating densities of insect herbivores in habitat patches with a constant area but varying numbers of plants. Using a mathematical model, predictions of scale-dependent immigration and emigration rates for insects into patches with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 73 publications
2
32
0
Order By: Relevance
“…The density responses of insects, however, may be highly variable, depending on how herbivore foraging biology affects migration rates between patches (Bowman et al 2002, Bukovinszky et al 2005, Hamba¨ck and Englund 2005 and how variation in plant traits, such as nutritional quality, interacts with insect movement and reproduction (see, e.g., Bukovinszky et al 2010, Hamba¨ck et al 2012. Ultimately, densities of herbivores on focal plants will depend on whether interactions with plant neighbors translate into frequency-dependent (associational) or density-dependent (concentration or dilution) effects on herbivore movement (Andersson et al 2013). Our results indicate the possible role of associational and dilution effects of AG-BG interactions on insect population densities.…”
Section: Discussionmentioning
confidence: 99%
“…The density responses of insects, however, may be highly variable, depending on how herbivore foraging biology affects migration rates between patches (Bowman et al 2002, Bukovinszky et al 2005, Hamba¨ck and Englund 2005 and how variation in plant traits, such as nutritional quality, interacts with insect movement and reproduction (see, e.g., Bukovinszky et al 2010, Hamba¨ck et al 2012. Ultimately, densities of herbivores on focal plants will depend on whether interactions with plant neighbors translate into frequency-dependent (associational) or density-dependent (concentration or dilution) effects on herbivore movement (Andersson et al 2013). Our results indicate the possible role of associational and dilution effects of AG-BG interactions on insect population densities.…”
Section: Discussionmentioning
confidence: 99%
“…First, associational resistance has been proposed to result primarily from a reduced ability of herbivores to locate and reach their host plants among heterospecific neighbors. This may be due to patches with greater plant diversity being less attractive than monospecific patches (i.e., the resource concentration hypothesis, Root, 1973;Andersson, Löfstedt, & Hambäck, 2013) or from heterospecific neighbors reducing the physical (Castagneyrol et al, 2013;Damien et al, 2016;Floater & Zalucki, 2000) or chemical (Jactel, Birgersson, Andersson, & Schlyter, 2011;Zhang & Schlyter, 2004) apparency of host plants. Alternatively, the attractant-decoy hypothesis predicts that herbivores can be diverted from a given plant and aggregate on more apparent, more attractive, or more palatable neighbors (Atsatt & O'Dowd, 1976;Hahn & Orrock, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…). Consequently, a stronger odour plume due to a higher density (or concentration) of resources will not necessarily result in a higher attraction of consumers (Bossert & Wilson ; Andersson, Löfstedt & Hambäck ; Beyaert & Hilker ) and could explain why many authors have found mixed results concerning the prediction of the resource concentration hypothesis that larger patches will attract more consumers (Root ; Bach ; Kunin ; Sholes ).…”
Section: Discussionmentioning
confidence: 99%